(untitled) (Economic and Political Thought, 2015)
The article analyses the attitudes of the Polish political parties towards the ‘Silesian issue’ based on their attitude towards Ruch Autonomii Śląska (RAŚ) [the Silesian Autonomy Movement]. Using the available data analysis as well as the method of individual semi-structured in-depth interviews, the paper provides up-to-date knowledge about the above-mentioned field. The predominant majority of Polish political parties (both at the central and the regional level) have a negative attitude towards RAŚ and its postulates – among others: the autonomy for the regions, recognition of the Silesians as a separate nation or the status of the Silesian language. The paper attempts to systematise the Polish political parties’ position on the ‘Silesian issue’ exemplified by their attitudes towards RAŚ.